Dietary acculturation among Filipino Americans Their meal patterns. - Narciso, M. H. (Compendium of Human Ecology Researches in the Philippines, 2003)
This paper investigated dietary acculturation among Filipino-Americans in United States of America through their meal patterns. There were 267 subjects, they were predominantly female (67 percent), middle aged (median age = 47), highly educated and stayed in the US for a median of 17 years. The Filipino-Americans studied appear to have adopted a bicultural set of food patterns. Their meal structure was traditional but content was largely reduced of cultural foods. Recommendations on addressing the probable or consequent loss of traditional food knowledge and skills were forwarded.